High rate of hepatitis C virus (HCV) recurrence in HIV‐infected individuals with spontaneous HCV RNA clearance. Issue 10 (11th May 2014) - Peters, L; Mocroft, A; Soriano, V; Rockstroh, JK; Kirkby, N; Reiss, P; Katlama, C; Zakharova, N; Flisiak, R; Lundgren, JD; ,
Abstract : Objectives: Following resolution of hepatitis C virus (HCV) infection, recurrence has been shown to occur in some persons with repeated exposure to HCV. We aimed to investigate the rate and factors associated with HCV RNA recurrence among HIV‐1‐infected patients with prior spontaneous HCV RNA clearance in the EuroSIDA cohort. Methods: All HIV‐infected patients with documented prior spontaneous HCV clearance, and at least one subsequently collected plasma sample, were examined. The last sample was tested for HCV RNA and those with HCV RNA ≥ 615 IU/mL were defined as having HCV recurrence and their characteristics were compared with those of patients who were still aviraemic. Logistic regression was used to identify factors associated with HCV recurrence. Results: Of 191 eligible patients, 35 [18.3%; 95% confidence interval (CI) 12.8–23.8%] had HCV recurrence. Thirty‐three (94.3%) were injecting drug users (IDUs). The median time between the first and last samples was 3.6 years (interquartile range 2.0–5.8 years). After adjustment, those on combination antiretroviral therapy [odds ratio (OR) 0.44; 95% CI 0.20–0.99; P = 0.046] and older persons (OR 0.51 per 10 years older; 95% CI 0.28–0.95; P = 0.033) were less likely to have HCV RNA recurrence, whereas IDUs were over 6 times more likely to have HCV RNA recurrence compared with non‐IDUs (OR 6.58; 95% CI 1.48–29.28; P = 0.013). Conclusions: Around 1 in 5 HIV‐infected patients with prior spontaneous HCV RNA clearance had detectable HCV RNA during follow‐up. Our findings underline the importance of maintaining focus on preventive measures to reduce IDU and sharing of contaminated needles. Clinicians should maintain a high degree of vigilance to identify patients with new HCV infection early.